Émergence d’un genre littéraire. La poésie subsaharienne de langue française des lendemains de la Seconde Guerre mondiale aux indépendances - Nadjia MERDACI (Altralang Journal, 2022)
Emergence of a Literary Genre: French-Language Sub-Saharan Poetry from The Aftermath of the Second World War to Independence